O processo de análise de assunto na catalogação de documentos: a perspectiva sociocognitiva do catalogador em contexto de biblioteca universitária - Redigolo, Franciele Marques [UNESP] (Universidade Estadual Paulista (Unesp), 2010)
The subject analysis is an intellectual process that depends on the professional cognitive and the domain of physical, psychological and sociocognitive contexts are necessary for the cataloger achieve the reading, identification and selection of concepts in the design oriented for content and the demand. The research of professional context of content treatment in university libraries is required for data collection and observation of the processes of professional subject catalogers with a view to further development of methodology for the subject cataloging of documents. It proposes the analysis of the procedures of subject analysis for examining on documents cataloging and the views of participants about the meanings of the results obtained in their daily practice from ethnographic research and use of the technique of Individual Verbal Protocol and interviews in the context of various university libraries in the field of Computer Science. It has as main objective to contribute to improving studies of the practice of subject analysis on cataloging in the context of university libraries in order to optimize the results of information retrieval in catalogs. In a view to implementing the proposal presented above, this research has as specifics objectives: a) provide theoretical and methodological study on the process of subject analysis in the thematic treatment with emphasis on the context of cataloging in university libraries, b) investigate processes of subject analysis on cataloging of documents, with Verbal Protocol, made by the cataloguer in the context of several university libraries, and c) identify issues, functions, processes and actions of daily practice of subject analysis on cataloging from the perspective of the cataloguer. Were performed six collections of data with the Individual Verbal Protocol, in the university libraries, whose observation provided the obtaining of ...(Complete abstract click electronic address below)

A análise de assunto é um processamento intelectual que depende da cognição profissional e o domínio do contexto físico, psicológico e sociocognitivo são necessários para que o catalogador realize a leitura, identificação e seleção de conceitos na concepção orientada para conteúdo e para a demanda. A investigação do contexto profissional de tratamento de conteúdo em bibliotecas universitárias é necessária para coleta de dados e observação dos processos dos profissionais catalogadores de assunto com vistas à futura elaboração de metodologia para catalogação de assunto de documentos. Propõe-se a análise dos processos de análise de assunto na catalogação de documentos e a visão dos participantes sobre os significados dos resultados obtidos em sua prática cotidiana a partir de pesquisa etnográfica e uso da técnica de Protocolo Verbal Individual e entrevistas em contexto de diferentes Bibliotecas Universitárias no domínio de Ciência da Computação. Possui como objetivo geral contribuir para estudos de aprimoramento da prática de análise de assunto na catalogação em contexto de Bibliotecas Universitárias com intuito de otimizar os resultados da recuperação da informação em catálogos.Tendo em vista a concretização da proposta apresentada acima, a presente pesquisa possui como objetivos específicos: a) Realizar estudo teórico e metodológico sobre o processo de análise de assunto no tratamento temático com enfoque no contexto da catalogação em bibliotecas universitárias; b) Investigar processos de análise de assunto na catalogação de documentos, com Protocolo Verbal, realizados pelo catalogador em contexto de diferentes Bibliotecas Universitárias; e c) Identificar aspectos, funções, processos e ações da prática cotidiana da análise de assunto na catalogação a partir da visão do catalogador. Foram realizadas as seis coletas de...
Keywords: Bibliotecas universitárias; Catalogação de assunto; Protocolo verbal; Análise de assunto; Tratamento temático da informação; Contexto sociocognitivo; Thematic Treatment of Information; Subject Analysis; Subject Cataloging; Socio-cognitive Context; Verbal Protocol; Ethnographic Research